2021
DOI: 10.1007/s13755-021-00147-7
|View full text |Cite
|
Sign up to set email alerts
|

Contact tracing apps for the COVID-19 pandemic: a systematic literature review of challenges and future directions for neo-liberal societies

Abstract: Purpose The COVID-19 pandemic has spread with increased fatalities around the world and has become an international public health crisis. Public health authorities in many countries have introduced contact tracing apps to track and trace infected persons as part of measures to contain the spread of the Severe Acute Respiratory Syndrome-Coronavirus 2. However, there are major concerns about its efficacy and privacy which affects mass acceptance amongst a population. This systematic literature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
104
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 98 publications
1
104
0
2
Order By: Relevance
“…During the COVID-19 pandemic, digital health and telemedicine solutions based on smartphone apps (socalled m-health) gained increasing popularity. Apps for digital contact tracings were used to collect and analyze data on people's proximity, location, movement, and health status [13] . When used at scale, particularly when integrating AI-based technologies, these helped contain the spread of the virus and mitigate the effect of COVID-19 on population health [13,14] .…”
Section: Main Applications Of Telemedicine During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, digital health and telemedicine solutions based on smartphone apps (socalled m-health) gained increasing popularity. Apps for digital contact tracings were used to collect and analyze data on people's proximity, location, movement, and health status [13] . When used at scale, particularly when integrating AI-based technologies, these helped contain the spread of the virus and mitigate the effect of COVID-19 on population health [13,14] .…”
Section: Main Applications Of Telemedicine During Covid-19mentioning
confidence: 99%
“…Apps for digital contact tracings were used to collect and analyze data on people’s proximity, location, movement, and health status [ 13 ] . When used at scale, particularly when integrating AI-based technologies, these helped contain the spread of the virus and mitigate the effect of COVID-19 on population health [ 13 , 14 ] . Other m-Health applications were used for symptom checking, remote monitoring, and video consultation, and they were also valuable means for health information dissemination and awareness raising in the population.…”
Section: Main Applications Of Telemedicine During Covid-19mentioning
confidence: 99%
“…There is an urgent need to establish a system for sharing and dispersing medical information so that patients can share their health data with their doctors for remote monitoring, and even with the public. In addition, as mentioned in [ 1 ], security vulnerabilities, user data privacy concerns, lack of transparency and other issues will affect the public’s acceptance of such information sharing applications. In order to ensure the public’s acceptance, such a data sharing system needs to ensure the authenticity of the data, that is, the data source is traceable, the transparency of the sharing mechanism, and the security and reliability of the sharing system.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cultural attitudes and social norms towards privacy have influenced the use of these systems to combat the pandemic [14][15][16]. In the case of Immuni, GDPR legal requirements are met by design.…”
Section: Introductionmentioning
confidence: 99%